E-Handball: Technology helps development - Sequeira, P.; Erichsen, L. (5th EHF Scientific Conference "Handball for Life", 21.-22.11.2019, Cologne, 2020)
Education plays a crucial role in the development of any Sport. Since the existence of the European Handball Federation, Education was always at the first stage of its mission. As in many others areas, also Education is evolving. With the new Technologies and it's tools it's now possible to teach in different ways that in the past did not exist. What EHF is doing in the present and thinking for the future is the purpose of this article.